1991
DOI: 10.1007/bf01400496
|View full text |Cite
|
Sign up to set email alerts
|

The transcallosal approach for lesions affecting the lateral and third ventricles

Abstract: The study was carried out on a series of 42 patients who underwent surgery through a midline approach. Lesions were in the anterior part of the third ventricle in 32 cases, in the frontal horns in 6, in the trigone in 3, and in both lateral and third ventricles in 1 case. The third ventricle was approached through Monro's foramen in 22 cases and through an interfornicial route in 9 cases. Surgical mortality occurred in 2 cases (5%). Permanent morbidity occurred in another 2 cases (5%): it consisted of slight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 28 publications
3
30
0
3
Order By: Relevance
“…29,32 There is evidence that a longitudinal callosotomy of up to 2 cm in the proximal region of the corpus callosum trunk does not cause significant neuropsychological changes, making the anterior transcallosal route a safe alternative for accessing ventricular lesions. 2,22,38,42 In the present study, we found a mean corpus callosum trunk thickness of approximately 10 mm, which was similar to that found in other studies. 19,31 Morphometric studies of individuals without neurological disease can most likely establish normal values of the corpus callosum subregions in a population to identify the presence and progression of a particular disease and to assist in the surgical planning of intraventricular lesions and some types of epilepsy.…”
Section: Figsupporting
confidence: 81%
See 3 more Smart Citations
“…29,32 There is evidence that a longitudinal callosotomy of up to 2 cm in the proximal region of the corpus callosum trunk does not cause significant neuropsychological changes, making the anterior transcallosal route a safe alternative for accessing ventricular lesions. 2,22,38,42 In the present study, we found a mean corpus callosum trunk thickness of approximately 10 mm, which was similar to that found in other studies. 19,31 Morphometric studies of individuals without neurological disease can most likely establish normal values of the corpus callosum subregions in a population to identify the presence and progression of a particular disease and to assist in the surgical planning of intraventricular lesions and some types of epilepsy.…”
Section: Figsupporting
confidence: 81%
“…The mean value of the working area of the transcallosal-transchoroidal approach was 121 mm 2 and that of the transcallosal-transforniceal-transchoroidal approach was 150 mm 2 . We therefore observed a mean increase of 29 mm 2 (p < 0.05) in working area after sectioning the fornix column ( Fig.…”
Section: Surgical Exposure Areamentioning
confidence: 99%
See 2 more Smart Citations
“…1) The transcallosal approach is suitable for small lesions or lesions attached to the surface of the thalamus, due to the low risk of fornical injury during tumor removal and the small callosal section, which may not cause any new damage to the higher cortical functions such as disconnection syndrome. 1,3,10) The risk of memory disturbance is similar for the two approaches, and permanent memory disturbance is considered to be attributable to preoperative cognitive dysfunction. 1) The transcortical approach carries the risk of postoperative seizure and subcortical fiber injury in the dominant frontal lobe.…”
Section: Discussionmentioning
confidence: 99%